Flavonoids in Juglans regia L. Leaves and Evaluation of In Vitro Antioxidant Activity via Intracellular and Chemical Methods - Ming-Hui Zhao; Zi-Tao Jiang; Tao Liu; Rong Li (The Scientific World Journal)
Flavonoids are rich in Juglans regia L. leaves. They have potent antioxidant properties, which have been related to regulating immune function and enhancing anticancer activity. Herein, qualitative and quantitative determination of flavonoids from J. regia leaves was carried out using high performance liquid chromatography coupled with tandem mass spectrometry with electrospray ionization and negative ion detection (HPLC-ESI-MS/MS) by comparison of the retention times and mass spectral fragments with standard substances or related literatures. Seventeen compounds were identified and major components are quercetin-3-O-rhamnoside (453.11 μg/g, dry weight), quercetin-3-O-arabinoside (73.91 μg/g), quercetin-3-O-xyloside (70.04 μg/g), kaempferol-O-pentoside derivative (49.04 μg/g), quercetin-3-O-galactoside (48.61 μg/g), and kaempferol-O-pentoside (48.46 μg/g). The in vitro intracellular antioxidation indicated that flavonoids from J. regia leaves could reduce the reactive oxygen species (ROS) level in RAW264.7 cells and showed good radical scavenging activities. These results proved to be more related to the flavonoids that could be considered in the design of new formulations of dietary supplements or functional foods.